Languages of the world an introduction - Pereltsvaig, Asya 1972- (Cambridge University Press, 2012)
"What do all human languages have in common and in what ways are they different? How can language be used to trace different peoples and their past? Are certain languages similar because of common descent or language contact? Assuming no prior knowledge of linguistics, this textbook introduces readers to the rich diversity of human languages, familiarizing students with the variety and typology of languages around the world. Linguistic terms and concepts are explained, in the text and in the glossary, and illustrated with simple, accessible examples. Eighteen language maps and numerous language family charts enable students to place a language geographically or genealogically. A supporting website includes additional language maps and sound recordings that can be used to illustrate the peculiarities of the sound systems of various languages. ?Test yourself? questions throughout the book make it easier for students to analyze data from unfamiliar languages"-- |c Provided by publisher.